Orangutans - Woods, Mae (Minneapolis, Minn. : Abdo & Daughters, 1998)
Describes the physical appearance and the behavior of the ape with the long red hair and the long arms that nearly touch the ground.
Includes bibliographical references and index.
Keywords: Orangutan -- Juvenile literature; Orangutan